Evaluating Expression of the STAG1 Gene as a Potential Breast Cancer Biomarker - Lafta, Inam J; Kudhair, Bassam K; Iyiola, Oluyinka A; Ahmed, Emad A; Chou, Tachung (The Iraqi Journal of Veterinary Medicine, 2021)
STAG proteins, which are part of the cohesin complex and encoded by the STAG genes, are known as Irr1/Scc3 in yeast and as SA/STAG/stromalin in mammals. There are more variants as there are alternate splice sites, maybe three open reading frames (ORFs) code for three main proteins, including: SA1 (STAG1), SA2 (STAG2) and SA3 (STAG3). The cohesin protein complex has various essential roles in eukaryotic cell biology. This study compared the expression of the STAG1 gene in four different breast cancer cell lines, including: MCF-7, T-47D, MDA-MB-468, and MDA-MB-231 and normal breast tissue. RNA was extracted from these cell lines and mRNA was converted to cDNA, and then expression of the STAG1 gene was quantified by three sets of specific primer pairs using Real Time-quantitative PCR (RT-qPCR). The findings show significantly different over-expression of STAG1 in these cancer cell lines in comparison with the normal tissue, and the cell lines were different in their expression levels. In conclusion, the STAG1 gene can be postulated as a candidate breast cancer biomarker that needs to be further evaluated in breast tumor biopsies.